1993
DOI: 10.21273/jashs.118.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrogel on Physical Properties of Coarse-structured Horticultural Substrates

Abstract: Addition of a polyacrylamide hydrogel to pine bark and pine bark + sand substrates had no effect on total porosity, regardless of incorporation rate. Container capacity was increased with increasing rate of hydrogel in both substrates. Air space in pine bark was slightly increased at the lowest rate but was reduced with higher incorporation rates. Air space in pine bark + sand was reduced with all hydrogel additions. The dry weigh', of hydrogel cubes recovered from both substrates was similar to amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 15 publications
1
70
0
10
Order By: Relevance
“…This might be attributed to the re-swelling of former dehydrated PAA structures by taking up water from the soil pore system and thus decreasing the relatively lower stabilization effects by its intrinsic structural properties and the soil pore water. It has been shown that hydrogels can re-absorb water to a certain degree, even under strongly restricted conditions such as confining particle and suction pressures (Fonteno and Bilderback, 1993;Sannino, 2008;Xu et al, 2006). All in all, although the soil pore water in the treated soil might have contributed to the structural stability as a result of an increased capillarity between the cemented soil particles, the effects of particle cementation and gluing by dehydrated and reswollen PAA structures seemed the predominant reason for the remaining and even re-increased stability after remoistening and additional incubation time of seven days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the re-swelling of former dehydrated PAA structures by taking up water from the soil pore system and thus decreasing the relatively lower stabilization effects by its intrinsic structural properties and the soil pore water. It has been shown that hydrogels can re-absorb water to a certain degree, even under strongly restricted conditions such as confining particle and suction pressures (Fonteno and Bilderback, 1993;Sannino, 2008;Xu et al, 2006). All in all, although the soil pore water in the treated soil might have contributed to the structural stability as a result of an increased capillarity between the cemented soil particles, the effects of particle cementation and gluing by dehydrated and reswollen PAA structures seemed the predominant reason for the remaining and even re-increased stability after remoistening and additional incubation time of seven days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogels have been successfully used as soil amendments in agriculture and horticulture industry in order to improve the water-holding capacity and/or nutrient retention of sandy soil [15,16] as comparable to clay or loam [17]. Superabsorbent hydrogels have the potential to influence soil permeability [18], density, structure, texture [19], evaporation [20] and infiltration rates of water through the soils [21].…”
Section: Introductionmentioning
confidence: 99%
“…Another method is the application of a matric potential by direct pressure reduction using a water column (Johnson and Veltkamp, 1985). The reproducibility of the results depends on the contact between hydrogel and the suction plate which is not self-evident (Fonteno and Bilderback, 1993). In this context, syneresis effects are an additional problem encountered for low matric potentials.…”
Section: Methods To Quantify Drying/swelling and Agingmentioning
confidence: 99%